Hepatic encephalopathy: pathogenesis, clinical presentation, diagnostics, treatment - Ch. S. Pavlov; I. V. Damulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2016)
The aim of review. To present modern concept on pathogenesis, clinical presentation, diagnostics and treatment of hepatic encephalopathy (HE). Summary. HE is a complex of neurological and psychiatric disorders that develop on a background of severe liver diseases due to portal blood shunting and impaired liver detoxication function. Expert opinions on the leading mechanism of HE pathogenesis are contradictory. Some believe, that the leading part is played by the effect of hyperammoniemia on neuronal functions; the others give major importance to the change in aminoacid spectrum and neurotransmitter disorders; the third give the most attention to elevation of mercaptan concentration and level of shortchain fatty acids, change of GABA-benzodiazepine complex function. HE is characterized by heterogeneity of manifestations. Cognitive (varying from the minimal changes to coma) and motor (muscles stiffness, baryphonia, tremor, etc.) disorders prevail in the clinical presentation. The basic approaches in treatment of HE include: detection and elimination liver damaging factors that provoke onset or stimulate progression of HE; reduction of production and absorption of ammonia or increase of its elimination. At frequently relapsing and progressing liver failure liver transplantation is performed. Conclusion. Involvement of the central nervous system at liver failure is the major problem from the point of view of duly and correct diagnostics, treatment, and social adaptation of patients. Many aspects of HE in particular its pathogenesis are insufficiently investigated.